Melatih Keseimbangan Anak Melalui Permainan Engklek di TK Harapan Bangsa - Saudah Saudah; Muzakki Muzakki; Lily Fazri Noviyanti (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to train children's balance through the game of hopscotch. This study uses a qualitative research method, data collection through three techniques, namely observation, interviews and documentation. The results of the study indicate that the game of hopscotch can train children's balance, which can be seen from the child's ability to perform body movements in a coordinated manner so that the child looks balanced, flexible and agile when playing hopscotch, in addition the child is also able to coordinate eye-foot-hand movements and play physical games with rules